2018
DOI: 10.3390/electronics7120372
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the FIR Filter Structure in Finite Residue Field Algebra

Abstract: This paper introduces a method for optimizing non-recursive filtering algorithms. A mathematical model of a non-recursive digital filter is proposed and a performance estimation is given. A method for optimizing the structural implementation of the modular digital filter is described. The essence of the optimization is that by using the property of the residue ring and the properties of the symmetric impulse response of the filter, it is possible to obtain a filter having almost a half the length of the impuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…All these attractive features increase interest to RNS in the areas where large amounts of computation are needed. The applications of RNS are digital signal processing [2][3][4], cryptography [5][6][7], digital image processing [8], cloud computing [9], Internet of Things [10] and others. In [11], the authors propose a technique to estimate real-valued numbers by means of the Chinese remainder theorem (CRT), employing for this goal a Kroenecker based M-Estimation, to improve robustness.…”
mentioning
confidence: 99%
“…All these attractive features increase interest to RNS in the areas where large amounts of computation are needed. The applications of RNS are digital signal processing [2][3][4], cryptography [5][6][7], digital image processing [8], cloud computing [9], Internet of Things [10] and others. In [11], the authors propose a technique to estimate real-valued numbers by means of the Chinese remainder theorem (CRT), employing for this goal a Kroenecker based M-Estimation, to improve robustness.…”
mentioning
confidence: 99%
“…Hardware simulation performed on FPGA Artix xc7a200tffg1156-3 in Xilinx Vivado 18.3 using VHDL hardware description language. The goal of the simulation was to compare the technical characteristics of the FIR DF implemented using known architectures in PNS [30] and in RNS [11,14] with the FIR DF using the proposed architecture in RNS with different moduli sets. Table V shows results of hardware simulation of 15th order FIR DF with different bit width.…”
Section: Hardware Simulation Of Digital Filters In the Residue Numentioning
confidence: 99%
“…The proposed method with 5modulus RNS allows to increase the frequency of the 15th order FIR DF by 2.0-4.2 times and reduce the hardware costs for its implementation by 1.1-2.6 times, with increasing power consumption by 7% -33% compared to the known method [30] based on PNS. Comparison with the known method [11] based on RNS with 5 moduli showed that proposed method allows to increase the frequency of the 15th order FIR DF by 1.6-4.4 times and reduce hardware costs for its implementation by 1.8-2.5 times with increasing power consumption by 11% -41%. The results of hardware simulation presented in Table VI show that use the proposed method of 3-modulus RNS allows to increase the frequency of FIR DF with = 16 by 1.9-2.2 times and reducing hardware costs for its implementation by 10% -44% with increasing power consumption by 6% -17% compared to the known method [30] based on PNS.…”
Section: Hardware Simulation Of Digital Filters In the Residue Numentioning
confidence: 99%
See 1 more Smart Citation
“…This fact follows from numerous publications dedicated to RNS usage in digital signal processing, image processing, antinoise coding, cryptographic systems, quantum automata, neurocomputers, systems with the massive parallelism of operations, cloud computing, DNA computing, etc. [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Of 17mentioning
confidence: 99%